FIP1L1-PDGFRA-Gene Fusion in Patients with Eosinophilia and Spinal Manifestation - Khan, Feroz Ali (International Journal of Pathology, 2020)
The rapid proliferation of progenitors of blood cells increases the chances of mutations and production of dysfunctional cells that often suppress the normal hematopoietic system. Chronic eosinophilic leukemia, characterized by elevated levels of pink-staining bilobed eosinophils, is one of the known pathological presentation of unregulated proliferation of dysplastic blood cells. Tissue infiltration of heart, lungs, skin, gut and other organs has been observed previously but the formation of a mass, comprising of myeloid and eosinophilic infiltrates, around the spinal cord has rarely been seen. With the spinal mass removed, our reported patient’s eosinophilia responded to short course of imatinib however, left him bed bound due to lower limbs paralysis.